Обеспечение гендерного равенства как важное направление реформ в современном Узбекистане (SCIENCE and SOCIETY, 2025)
In the article the author examines issues of gender equality. How are these issues resolved at the state level? An analy- sis of sources that covered equality issues in their publications is carried out. And now this issue is at the state level.